Cohort Study in Outcome and One-Year Mortality of Acute Stroke Patient in Academic Hospital Universitas Gadjah Mada - Maskuri, Fajar; Tyas, Humaera Elphananing; Talirasa, Nimitta; Wiastuti, Arni; Akhsani, Fathiya; Pratama, Yanasta Yudo (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
Background: Stroke is still becoming one of the most common non-communicable diseases in Indonesia. Sample Registration System survey in 2016 showed that in Indonesia stroke has become the most common cause of death at all age, about 19.9%. 4 Research conducted by Novbakht found that age, sex, BMI, type of stroke, family history of stroke, hyperlipidaemia, diabetes, and severity of stroke was related and increased the mortality rate. 6 Academic Hospital Universitas Gadjah Mada had not conducted this type of research, so that researcher wanted to know the one-year mortality rate after stroke, factors that related to mortality, and to improve the quality of stroke treatment at Academic Hospital Universitas Gadjah Mada.Objective: To know one-year mortality rate in acute stroke patients in Academic Hospital Universitas Gadjah Mada by looking for the acute stroke characteristic, outcome of stroke patients, and risk factors that cause mortality in stroke patients.Method: This is an analytic research using retrospective cohort study through data collection of acute stroke patients (patients with <5 days stroke onset) during July 2019 until June 2022 then we followed up the condition in the first year after stroke by using medical records, direct examination, or via telephone or video call. Mortality rates were assessed one year after stroke and the predictors of death were evaluated using the cox proportional hazard model.Result: One-year mortality after stroke in our study were related to age (>67 years old) (OR=2,29; 95% CI 1,18-4,46; p=0,015) and the severity of stroke was related to higher NIHSS score (NIHSS score during admission 16-42, (OR=38,49; 95% CI 8,92-166,0; p<0,001)) and ICU admission ((OR=8,01; 95% CI 4,03-15,90; p<0,001)). Conclusion: An association was found between stroke severity and one-year outcomes of acute stroke patients with old age (>67 years), high NIHSS scores, and ICU admissions